A Control System Using Speech Recognition AMR in Robotic System - Bakri, Adil; Guerzou, Mokthar; Krobba, Ahmed (International Journal of Membrane Science and Technology, 2023)
Voice command is currently a vital task for developing smart assistive devices, especially since the frequency of accidents continues to climb, posing a huge shift in handicapped people’s lifestyles which makes producing a material to support them in their daily lives a significant challenge. One of the proposed options is to add an embedded system with a machine learning algorithm represented by voice recognition to assist handicapped people. In this paper, we have implemented a voice command control system in Arabic through an AMR Voice application in Smartphone with a microcontroller demonstrates a sophisticated integration of hardware and software technologies. The utilization of Bluetooth technology which acts as a communication channel with the LED light circuit , which will then be connected to the Arduino to create a system based on voice commands.